Visual Studio 2010 all-in-one for dummies - Moore, Andrew (--For dummies., 2010)
"Visual Studio is Microsoft's comprehensive development environment that encompasses the .NET Framework, various programming languages, and ASP.NET. Programmers love it for developing applications for mobile devices and the Web. Because Visual Studio can be complex, the All-in-One For Dummies format makes it easy for beginners to grasp its different parts and get up to speed. Visual Studio 2010 All-in-One For Dummies provides both a great instruction book for new programmers and a valuable reference for the more experienced"--Resource description page.